JERAPAN DEBU DAN PARTIKEL TIMBAL (Pb) OLEH DAUN BERDASARKAN LETAK POHON DAN POSISI TAJUK: STUDI KASUS JALUR HIJAU Acacia mangium, JALAN TOL JAGORAWI - Rachmad Hermawan; Cecep Kusmana; Nizar Nasrullah; Lilik Budi Prasetyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2011)
Tree locations and crown positions was assumed to have effects on adsorption of dust and Pb particles by leaves. The objectives of the research were: (a) to determine the effects of tree locations and crown positions on adsorption of dust and Pb particles of leaves in roadside vegetation; (b) to determine the pattern of dust and Pb particle adsorption of leaves in roadside vegetation; (c) to determine correlation between dust and Pb concentration. Leaves samples was taken from the front and back part of the crown of three trees from each of the first three rows of the roadside vegetation. The samples were used to analysis dust and Pb concentration. The results showed that tree locations and crown positions affected adsorption of dust and Pb concentration of leaves. There was no interaction between tree locations and crown positions, but there was a decreasing trend from front part of the crown of trees1 until back part of the crowns of tress3. There was a correlation (R2= 0,755) between dust concentrations and Pb concentrations with equation of Y= 0,1403X-41,686 (Y= Pb concentration ; X= dust concentration). Keywords: roadside vegetation, Pb, dust, concentration, adsorption